2017
DOI: 10.1111/exd.13315
|View full text |Cite
|
Sign up to set email alerts
|

Induced histamine regulates Ni elution from an implanted Ni wire in mice by downregulating neutrophil migration

Abstract: Histamine regulates various inflammatory reactions. We have reported that the expression of histidine decarboxylase (HDC) was induced by subcutaneous implantation of nickel (Ni) wire. However, the source and functions of histamine in Ni elution and Ni wire-induced inflammation have not been completely studied. We aimed to elucidate the effects of de novo synthesized histamine on leucocyte infiltration and Ni elution. Implantation of Ni wire induced an increase in the Ni ion content of the surrounding tissues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It has been shown that histamine inhibits neutrophil mobility via H2R signaling. 26 We observed that H2R deficiency promoted random migration, as well as fMLP-mediated chemotaxis, in both HDNs and LDNs (Figure 10E). This is in line with the in vivo phenotype, in that more neutrophils infiltrated the areas of intestinal inflammation and colonic tumors.…”
Section: Q29mentioning
confidence: 86%
“…It has been shown that histamine inhibits neutrophil mobility via H2R signaling. 26 We observed that H2R deficiency promoted random migration, as well as fMLP-mediated chemotaxis, in both HDNs and LDNs (Figure 10E). This is in line with the in vivo phenotype, in that more neutrophils infiltrated the areas of intestinal inflammation and colonic tumors.…”
Section: Q29mentioning
confidence: 86%
“…Particularly, Gcsf , whose expression is increased with age in wild‐type mice is decreased in HDC‐KO mice (Figure 7e). This might be directly regulated by HDC expression because high HDC‐expressing myeloid cells are reported to differentiate into granulocytes during inflammation, and these cells simultaneously produce histamine, which enhances HSC dormancy and controls HSC differentiation through the H2 receptor (Kishimoto et al, 2017). Our data thus suggest that expression of these cytokines plays pivotal roles in maintaining a hematopoietic microenvironment in the liver of postnatal mice and that these may be regulated by histamine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of Zn 2+ at physiological concentrations were also observed in an in vivo model. We had reported that Ni 2+ elution from the Ni wire induced inflammatory events, such as neutrophil infiltration and prostaglandin and histamine production 5 , 6 , and that the initial inflammatory responses induced further elution of Ni 2+ 5 . Using the Ni wire-implanted mouse model, we showed that Ni 2+ -induced inflammation was enhanced in a Zn-deficient state.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the prevention of neointima formation by Ni-free stainless stent was demonstrated 4 . We also reported that the implantation of an Ni wire subcutaneously into the back of mice induced the elution of Ni 2+ , the expression of several inflammatory proteins such as cyclooxygenase-2 (COX-2) and neutrophil chemokine macrophage inflammatory protein-2 (MIP-2, CXCL2), and leukocyte infiltration as the initial responses 5 , 6 . Importantly, infiltration and activation of neutrophils enhanced further elution of Ni 2+ 5 .…”
Section: Introductionmentioning
confidence: 98%